Relationship Between Basic Trauma Cardiac Life Support (BTCLS) Knowledge With Nurse Skills in Doing Initial As-sessment in The Emergency Room - Rahmawati, Ida; Giena, Vike Pebri; Keraman, Buyung; Haryanti, Nimi (Sahabat Publikasi Kuu, 2023)
Background: The handling of emergency patients is very important for a nurse to master, because quick, precise and accurate actions will determine the patient's survival. Delay in handling in just a minute greatly affects the prognosis because brain injury and heart systems in a long time can cause biological death while clinical death can occur afterwards. Purpose : This study aims to study the relationship between BTCLS (Basic Trauma Cardiac Life Support) knowledge and skills in performing an initial assessment in the emergency room. Methods: This study used a cross sectional approach. The population in this study were all nurses in the emergency room of RSUD Dr. M. Yunus Bengkulu. The sampling technique used total sampling with a total of 31 nurses. This study used primary data obtained from filling out a nurse's knowledge questionnaire regarding BTCLS and observation using a checklist to assess the initial assessment. Results: The level of knowledge about BTCLS in the low was 1 person (3.2%), fair knowledge of BTCLS was 10 people (32.3%), and good knowledge of BTCLS was 20 people (64.5%). The skills of nurses in carrying out the initial assessment were found in the low category of 5 people (16.1%), fair category for 10 people (32.3%), and good for 16 people (51.6%). This study used the Somers'd test to obtain a correlation coefficient = 0.391 with a p-value = 0.013 <0.05 which is significant, then Ho is rejected and Ha is accepted. Conclusion: There is a relationship between nurses' knowledge about BTCLS with skills in conducting initial assessments in the emergency room. Because the value of the correlation coefficient lies in the interval 0.20-0.40, the relationship category is weak.